2013
DOI: 10.2478/s11535-013-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Ras and Ras mutations in cancer

Abstract: Ras genes are pre-eminent genes that are frequently linked with cancer biology. The functional loss of ras protein caused by various point mutations within the gene, is established as a prognostic factor for the genesis of a constitutively active Ras-MAPK pathway leading to cancer. Ras signaling circuit follows a complex pathway, which connects many signaling molecules and cells. Several strategies have come up for targeting mutant ras proteins for cancer therapy, however, the clinical benefits remain insignif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 132 publications
0
13
0
4
Order By: Relevance
“…HDACiassists caspase-3, -7 and -8 activations (Rajasekharan and Raman, 2013). The study results (Table 1, 2 and Figure 3) shown that there are no mutation on H-Ras gene myeloma cell since the H-Ras expression on the cell without any addition of C. mangga Val.…”
Section: Resultsmentioning
confidence: 82%
“…HDACiassists caspase-3, -7 and -8 activations (Rajasekharan and Raman, 2013). The study results (Table 1, 2 and Figure 3) shown that there are no mutation on H-Ras gene myeloma cell since the H-Ras expression on the cell without any addition of C. mangga Val.…”
Section: Resultsmentioning
confidence: 82%
“…In the heart, 66.7% of cardiac-specific genes are in the center of one compartment (marked compartment A), while 66.1% of liver-specific genes are toward the periphery in compartment B. The locations of the Ras isoforms on the human chromosomes also differ (Pellicer 2011 ; Rajasekharan and Raman 2013 ): HRAS gene is localized to the short arm (p) of chromosome 11 at position 5, the KRAS gene is located on the p arm of chromosome 12 at position 12.1, and the NRAS gene is on chromosome 1 at position 13.2. Even though these are positions along the linear chromosome sequence organization, and to date data about their 3D locations are unavailable, the distinct locations of isoforms suggest distinct organization and expression patterns.…”
Section: Differential Ras Isoform Expressionmentioning
confidence: 99%
“…The MAPK cascade consists of serine/threonine kinases, which convert extracellular molecules such as growth factors, hormones, tumor-promoting substances and differentiating factors, into intracellular signals for regulating cell proliferation, differentiation and survival [2]. The phosphorylated Raf1, an MAP3K, in turn activates MEK [3]. The guanine nucleotide exchange factors (GEFs) carry GTP to the RAS molecule, which becomes activated upon the changing of GDP for GTP [4].…”
mentioning
confidence: 99%
“…The cells that lack the p53 tumor suppressor gene are particularly affected by these consequences of RAS mutations, as p53 functions against the RAS oncogene [6]. It has been determined that RAS mutations are more prevalent in certain cancers but less likely associated with others, such as breast cancer [3]. Instead, most breast cancers, including ductal and lobular, are characterized by overexpression of the RAS protein [3].…”
mentioning
confidence: 99%